Summary of Research and Development of Intelligent Combustion Optimization System. Issue 6 (May 2019) - Xi, Yan; Kun, Lu; Kai, Wang
Abstract: This paper summarizes the purpose and significance of intelligent combustion optimization, and mainly introduces the theoretical research on intelligent combustion optimization algorithm and the development and application of intelligent combustion optimization system software. It makes a comprehensive assessment to the research results and technology development of intelligent combustion optimization, and gives an in-depth analysis of the current challenges and future development direction of intelligent combustion optimization technology. Finally, considering the latest research results and the current domestic thermal power development situation, it points out the urgency and necessity of the development of intelligent combustion optimization system.